Percutaneous Coronary Intervention: The Trends and Development - Muhammed Kashif Shaikh, Syed Zulfiquar Ali Shah, Ishrat Bibi, Tahira Junejo, Syed Jahanghir, Ayesha Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Ischemic heart disease causes mortality and disability worldwide. At the turn of the 21st century, shifting demographics have made it a serious issue in emerging nations. In high-income nations, the prevalence of coronary artery disease (CAD) is reducing due to increased government expenditure on awareness, education, disease knowledge, and treatment techniques1. Andreas Gruentzig’s 1976 coronary balloon angioplasty launched interventional cardiology. Technological advances, enhanced accomplishment, and fewer complications made this new technique a most common method of coronary revascularization, surpassing CABG2. Percutaneous coronary intervention (PCI) was retitled after coronary angioplasty tools expanded over time. Interventional cardiology has evolved less in the last 10 years than in the preceding 25, which were driven by technology, but we now know how to use PCI optimally. "What we should do" ruled this time. Peripheral vascular and structural cardiovascular disease interventions have grown and may dominate the future. Interventional cardiology’s future will be discussed alongside recent practice changes3,4.